(untitled) (Sudurpaschim Spectrum, 2026)
The involvement of the online learning materials for teaching learning activities has expanded rapidly throughout the world. In context of Nepal as well, the shift is noticed gradually. However, its access and effective use of it remain uneven due to several factors especially in rural areas. This study examines the digital divide that is access to online learning materials among secondary level students at Daneshwar Secondary School at Barakot, Baitadi district. Following the qualitative case study design, the researcher draws on in-depth interviews with students and teachers, focus group discussion and school-level observations to explore lived experiences of digital learning in a resource-constrained schools. The finding of the study shows that poor internet connectivity, lack of digital tools, irregular electricity supply, lack of digital literacy among both students and teachers are some of the hinderances for effective access to online learning materials. Their strong willingness to be connected with the digital learning students and teachers employ several strategies like, offline downloading of materials, peer support, device sharing and blending traditional teaching with the limited digital access having classroom. In order to develop strong digital connectivity in such rural areas there is need for context -specific policies.